Dynamic and static biomechanical traits of cardiac fibrosis - Liu, Han; Fan, Pengbei; Jin, Fanli; Huang, Guoyou; Guo, Xiaogang; Xu, Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiac fibrosis is a common pathology in cardiovascular diseases which are reported as the leading cause of death globally. In recent decades, accumulating evidence has shown that the biomechanical traits of fibrosis play important roles in cardiac fibrosis initiation, progression and treatment. In this review, we summarize the four main distinct biomechanical traits (i.e., stretch, fluid shear stress, ECM microarchitecture, and ECM stiffness) and categorize them into two different types (i.e., static and dynamic), mainly consulting the unique characteristic of the heart. Moreover, we also provide a comprehensive overview of the effect of different biomechanical traits on cardiac fibrosis, their transduction mechanisms, and in-vitro engineered models targeting biomechanical traits that will aid the identification and prediction of mechano-based therapeutic targets to ameliorate cardiac fibrosis.